Stress and associated factors of caregivers of elderly medical inpatients at King Chulalongkorn Memorial Hospital - Chumnisart, Rattanaporn; Tunvirachaisakul, Chavit (Chulalongkorn Medical Journal, 2022)
Background: Parallel with the increasing number for elderlies, the need of care when they were acutely ill has multiplied, with caregivers being tasked from the beginning to the end of the illness. A family member was often a primary person to take care of the elderly. This role might affect their mental health and quality of life. Objective: To explore the progression of stress and the associated factors among caregivers of the elderlies admitted with acute illness. Methods: This longitudinal descriptive study examined various factors associated with caregivers of the elderlies who were admitted to the medical wards of King Chulalongkorn Memorial Hospital. The study used structured questionnaires to elicit demographic information of the caregivers and the elderlies, Caregiver Strain Index (CSI), the Thai version of quality of life assessment (SF-36), and activities of daily living assessment (ADL) when the elderlies were admitted. Participated caregivers were then followed at one and three months using the CSI. Results: One hundred caregivers were enrolled in the study. The majority of caregivers had an level of stress and had a good quality of life. The highest average score of stress was at the baseline (score 4.7). Factors positively related to stress of caregivers were age of caregivers and being a family member of elderly (as opposed to being a professional caregiver) was related to the CSI score. The quality of life was negatively associated with the stress and could predict the decrease of stress in caregivers of elderly patients. Conclusion: Most caregivers of elderly patients had a good quality of life which was a protective factor in stress of caregivers in elderly patients. Age of caregivers and being a family member could help related parties promote caregivers’ mental health.